Deletion of aldose reductase from mice inhibits diabetes-induced retinal capillary degeneration and superoxide generation. - Jie Tang; Yunpeng Du; J Mark Petrash; Nader Sheibani; Timothy S Kern (PLoS ONE, 2013)
Pharmacologic inhibition of aldose reductase (AR) previously has been studied with respect to diabetic retinopathy with mixed results. Since drugs can have off-target effects, we studied the effects of AR deletion on the development and molecular abnormalities that contribute to diabetic retinopathy. Since recent data suggests an important role for leukocytes in the development of the retinopathy, we determined also if AR in leukocytes contributes to leukocyte-mediated death of retinal endothelial cells in diabetes.Wild-type (WT; C57BL/6J) and AR deficient (AR(-/-)) mice were made diabetic with streptozotocin. Mice were sacrificed at 2 and 10 months of diabetes to evaluate retinal vascular histopathology, to quantify retinal superoxide production and biochemical and physiological abnormalities in the retina, and to assess the number of retinal endothelial cells killed by blood leukocytes in a co-culture system.Diabetes in WT mice developed the expected degeneration of retinal capillaries, and increased generation of superoxide by the retina. Leukocytes from diabetic WT mice also killed more retinal endothelial cells than did leukocytes from nondiabetic animals (p<0.0001). Deletion of AR largely (P<0.05) inhibited the diabetes-induced degeneration of retinal capillaries, as well as the increase in superoxide production by retina. AR-deficiency significantly inhibited the diabetes-induced increase in expression of inducible nitric oxide synthase (iNOS) in retina, but had no significant effect on expression of intercellular adhesion molecule-1 (ICAM-1), phosphorylated p38 MAPK, or killing of retinal endothelial cells by leukocytes.AR contributes to the degeneration of retinal capillaries in diabetic mice. Deletion of the enzyme inhibits the diabetes-induced increase in expression of iNOS and of superoxide production, but does not correct a variety of other pro-inflammatory abnormalities associated with the development of diabetic retinopathy.